2019
DOI: 10.21608/alexja.2019.41854
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Beneficial Soil Microorganisms Enhanced the Growth and Efficiently Reduced Lead Content in Leaves of Lettuce (Lactuca sativa L.) Plant under Lead Stress

Abstract: Two pots experiments were conducted, during two successive winter seasons of 2016/2017 and 2017/2018, to test the role of biofertilizer inoculations (arbuscular mycorrhizal fungi, AMF; Bacillus megaterium, B. megaterium; and their mixture) in improving growth and quality of lettuce (Lactuca sativa L. cv. Balady) under different levels (0, 100, 200 and 300 ppm) of lead (Pb). The results illustrated that the growth and quality of lettuce were greatly affected by the escalated levels of Pb in soil. Clearly, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Liu et al [28] and Al Mamun et al [6] showed that plants accumulated less Cd in alkaline soils than acidic soils. The pH of Egyptian soil is generally in the alkaline range (7.7-8.3) [27,29,30]. Accordingly, the pH of the tested field sites ranged between 8.1 and 8.27 in both seasons, without significant differences between the four sites (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [28] and Al Mamun et al [6] showed that plants accumulated less Cd in alkaline soils than acidic soils. The pH of Egyptian soil is generally in the alkaline range (7.7-8.3) [27,29,30]. Accordingly, the pH of the tested field sites ranged between 8.1 and 8.27 in both seasons, without significant differences between the four sites (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The relative chlorophyll contents of globe artichoke leaves were measured using the SPAD-502 chlorophyll meter device (Konica Minolta Sensing, Japan) (Brengi and Abouelsaad, 2019;Hassan and Ali, 2019) . Methods previously published by Page et al (1982) , John (1970) , andCottenie et al (1982) were used to measure nitrogen (N), phosphorous (P), and potassium (K) contents (% D.W.), respectively, in heads and leaves from each treatment.…”
Section: Chemical Constituents Of Leaves and Headsmentioning
confidence: 99%
“…This eases the uptake of Cd by the roots to take up and send Cd to the leaves through the xylem ( Saidi et al., 2014 ). Trace concentrations of Cd can induce metal toxicity symptoms in plants ( Sary Hassan and Ibrahim Ali, 2019 ). Cadmium complicates the absorption of essential nutrients by plants and accumulates considerably disease in plants ( Usman et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%